Maternal Psychological Control and Rural Left-Behind Children's Anxiety: The Moderating Role of Externalizing Problem Behavior and Teacher Support - Deng, Na; Bi, Hongyan; Zhao, Jinxia (Frontiers in Psychology, 2021)
Based on the risk and protective factor framework and context-dependent theory, the present study investigated the association between maternal psychological control and anxiety among left-behind children in rural China as well as the moderating roles of externalizing problem behavior and teacher support in this association. A total of 149 children with two migrant parents, 306 children with only a migrant father, and 287 accompanied children aged 11–16 years (M = 13.85 years, SD = 0.50) in the rural areas of Shandong Province, Eastern China, participated in the study. Children reported their perceived levels of maternal psychological control, teacher support, externalizing problem behavior, and anxiety. The results provided evidence that a higher level of psychological control was associated with more anxiety symptoms in all three groups of children, and this association was stronger in children with two migrant parents than in accompanied children. Hierarchical regression analysis supported our hypotheses that the moderating effects of externalizing problem behavior and teacher support varied as a function of parents' migrant status, with externalizing problem behavior exacerbating the impact of psychological control on anxiety in accompanied children, and teacher support buffering the impact of psychological control on anxiety in children with a migrant father. These findings broaden our understanding of the factors and processes that contribute to anxiety problems in left-behind children in rural China.